IMPLEMENTASI PERAK SEHAT: INTEGRASI EDUKASI GIZI KLINIK, LEAFLET KODE QR, DAN DEMONSTRASI MASAK PANGAN LOKAL UNTUK PENCEGAHAN STUNTING - Yasinta Indah Widyaningsih; Jasmin Ambas; Andi Nurzakiah Amin; Mahendri Deayu Putri; Nurfalia Harfah (Universitas Mataram, 2026)
Stunting is a chronic nutritional problem that affects children's physical growth and cognitive development, particularly during the first 1,000 days of life. The contributing factors include unbalanced nutrient intake, inadequate parenting practices, recurrent infections, and limited access to healthcare services. Preventing stunting requires a comprehensive strategy that enhances knowledge, fosters positive attitudes, and strengthens balanced nutrition practices within the community. This community service activity, titled “Implementation of PERAK SEHAT: Integration of Clinical Nutrition Education, QR Code Leaflets, and Local Food Cooking Demonstrations for Stunting Prevention,” aimed to improve participants’ knowledge, attitudes, and behavioral intentions related to balanced nutrition. The methods employed included interactive lectures, group discussions, and cooking demonstrations using local food ingredients, involving pregnant women, mothers of toddlers, and adolescent girls in Bonto Perak Village, Pangkajene and Islands Regency. Evaluation was conducted through pre-test and post-test assessments to measure changes in knowledge, attitudes, and behavioral intentions. The results showed an increase in participants’ knowledge, positive attitude shifts, and stronger commitment to applying balanced nutrition principles. The digital leaflet served as a reinforcing medium that enabled participants to revisit the information at home. In conclusion, this activity proved to be an effective public health promotion strategy by integrating education and practical application to encourage positive behavioral changes related to balanced nutrition as an effort to prevent stunting.